2015
DOI: 10.1016/j.cemconres.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Chemical acceleration of a neutral granulated blast-furnace slag activated by sodium carbonate

Abstract: This paper presents results of a study on chemical acceleration of a neutral granulated blastfurnace slag activated using sodium carbonate. As strength development of alkali-activated slag cements containing neutral GBFS and sodium carbonate as activator at room temperature is known to be slow, three accelerators were investigated: sodium hydroxide, ordinary Portland cement and a combination of silica fume and slaked lime. In all cements, the main hydration product is C-(A)-S-H, but its structure varies betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(54 citation statements)
references
References 37 publications
5
49
0
Order By: Relevance
“…Kovtun et al [29] found that the intensity of gaylussite decreased in all accelerated pastes using accelerators such as sodium hydroxide and cement. The formation of hydrotalcite is also observed at the early ages but with only weak reflections (Fig.…”
Section: Xrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Kovtun et al [29] found that the intensity of gaylussite decreased in all accelerated pastes using accelerators such as sodium hydroxide and cement. The formation of hydrotalcite is also observed at the early ages but with only weak reflections (Fig.…”
Section: Xrdmentioning
confidence: 99%
“…As reported by Bernal et al [4] and our previous study [26], CO 3 2-anions concentration in the pore solution and the initially precipitated calcium carbonate significantly control the sodium carbonate activation process. According to the previous researches [4,23,[28][29][30] The present research aims to study the effect of LP on the reaction kinetics, reaction products and strength development of sodium carbonate activated slag. The heat evolution of mixtures with different LP incorporation levels was measured, up to 7 days.…”
Section: Introductionmentioning
confidence: 99%
“…There is a good consensus that, at early times of reaction, calcium and mixed sodium-calcium carbonates are the predominant crystalline reaction products forming in sodium carbonate-activated slag cements [11,29,30], instead of strength-giving phases such as calcium silicate hydrates (C-S-H). At advanced times of curing, formation of a highly cross-linked C-A-S-H type phase with a relatively low content of Ca in the outer product has been reported [28,31,32], providing strength to the hardened material.…”
Section: Sodium Carbonate Activated Slag Cementsmentioning
confidence: 99%
“…Several aluminosilicate sources are being studied to produce alkali-activated binders such as fly ash from thermoelectric power plants [10,13], metakaolin [14], spent fluid catalytic cracking catalysts [9], blastfurnace slag [15] and others. In addition, residues from the agroindustry are being researched in alkaliactivated binders, such as rice husk ash [16].…”
Section: Introductionmentioning
confidence: 99%